Bioelectrocatalytic Cofactor Regeneration Coupled to CO2 Fixation in a Redox‐Active Hydrogel for Stereoselective C−C Bond Formation. Issue 38 (7th July 2021) - Castañeda‐Losada, Leonardo; Adam, David; Paczia, Nicole; Buesen, Darren; Steffler, Fabian; Sieber, Volker; Erb, Tobias J.; Richter, Michael; Plumeré, Nicolas
Abstract: The sustainable capture and conversion of carbon dioxide (CO2 ) is key to achieving a circular carbon economy. Bioelectrocatalysis, which aims at using renewable energies to power the highly specific, direct transformation of CO2 into value added products, holds promise to achieve this goal. However, the functional integration of CO2 ‐fixing enzymes onto electrode materials for the electrosynthesis of stereochemically complex molecules remains to be demonstrated. Here, we show the electricity‐driven regio‐ and stereoselective incorporation of CO2 into crotonyl‐CoA by an NADPH‐dependent enzymatic reductive carboxylation. Co‐immobilization of a ferredoxin NADP + reductase and crotonyl‐CoA carboxylase/reductase within a 2, 2′‐viologen‐modified hydrogel enabled iterative NADPH recycling and stereoselective formation of (2S)‐ethylmalonyl‐CoA, a prospective intermediate towards multi‐carbon products from CO2, with 92±6 % faradaic efficiency and at a rate of 1.6±0.4 μmol cm −2  h −1 . This approach paves the way for realizing even more complex bioelectrocatalyic cascades in the future. Abstract : Electrified CO2 fixation switched on! In a bioelectrocatalytic approach an NADPH recycling module and a C−C bond formation module were co‐immobilized within a viologen‐based redox hydrogel. This enabled the regio‐ and stereoselective incorporation of CO2 into crotonyl‐CoA, yielding the most complex product known in bioelectrocatalytic CO2 conversion so far.